Is there a return–risk link in education? - Pereira, Pedro Telhado (2021)
Using results for 16 countries, the positive relationship between return to education and the risk involved in this investment is studied. It seems that most of the countries fit the pattern well: higher risk–higher return and the tradeoff is rather large.